Estimation of the Internal Adjustment Costs Model Using Longitudinal Establishment Data - Lichtenberg, Frank R. (The Review of Economics and Statistics, 1988)
-This paper develops estimates of the internal costs (measured in terms of foregone current output) associated with the introduction of new plant and equipment into manufacturing establishments, using the Census Bureau's Longitudinal Establishment Data file, a very large and rich source of production and investment data. Our estimates provide strong support for the internal-adjustment-costs hypothesis; they indicate that one-dollar increases in expansion and replacement investment cause, on the average, 35and 21-cent reductions, respectively, in current output. The internal cost of adjusting to equipment appears to be higher than the cost of adjusting to plant.